Implementation of AHP method in decision support system for AC brand selection at PT. Gemilang - Haris, Muhammad; Zulherry, Andi; Limbong, Isman Efendi; Tanjung, Mahardika Abdi Prawira (Journal of Intelligent Decision Support System (IDSS), 2024)
The selection of the optimal AC brand for PT Gemilang faces complex challenges as it involves the evaluation of various criteria such as quality, cost, energy efficiency, and after-sales service. This research aims to apply the Analytic Hierarchy Process (AHP) method to determine the best AC brand based on these criteria. The AHP method is used to develop a comparison matrix, calculate the weights of criteria and alternatives, and check the consistency of the results. The analysis results show that Brand B has the highest final weight, making it the most optimal choice compared to the other alternatives. The implications of this study show that the AHP method can be effectively used for multi-criteria decision-making in product selection, providing data-driven recommendations and reducing subjective bias in the selection process. This research makes a significant contribution to a more structured decision-making practice at PT Gemilang.